2020
DOI: 10.1530/rep-19-0268
|View full text |Cite
|
Sign up to set email alerts
|

The role of basigin in reproduction

Abstract: Basigin is a highly glycosylated transmembrane protein that was originally identified as a product of tumor cells. Basigin is a potent inducer of matrix metalloproteinases (MMPs) and angiogenic factors such as vascular endothelial growth factor (VEGF). Basigin is also a chaperone protein for specific metabolite transporters in the plasma cell membrane such as the monocarboxylate transporters and is an important regulator of cell metabolism. Studies in reproductive model systems have demonstrated that basigin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 112 publications
0
7
0
1
Order By: Relevance
“…It has been linked to the physiology and pathology of various reproductive processes. 4 Systematic CD147 knockout leads to perinatal lethality before day 12.5 of gestation in mice. 5 The observations could be due to deficiency of CD147 in the foetus and/or the placenta.…”
Section: E T T E R T O E D I T O R Dysregulation Of the Cd147 Complex...mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been linked to the physiology and pathology of various reproductive processes. 4 Systematic CD147 knockout leads to perinatal lethality before day 12.5 of gestation in mice. 5 The observations could be due to deficiency of CD147 in the foetus and/or the placenta.…”
Section: E T T E R T O E D I T O R Dysregulation Of the Cd147 Complex...mentioning
confidence: 99%
“…CD147 has an unusual transmembrane domain characterised by a single-charged glutamic acid in the hydrophobic transmembrane region, which promotes proteinprotein interactions. 4 CD147 is a component of two receptor complexes (Figure 3F; Table S2) on the plasma membrane of human EVCT. The CD147-integrin β1 interaction within the complex was confirmed by protein interaction analysis (Figure 3F), coimmunoprecipitation (Figure 3G) and their specific expression in EVCT (Figures S1C and S4).…”
Section: E T T E R T O E D I T O R Dysregulation Of the Cd147 Complex...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, DPP4 has been shown to be expressed on placental EVTs suppressing their invasion [ 81 ]. Also, CD147, the third suggested entry receptor for SARS-CoV-2 [ 54 ], plays various important physiological roles in reproductive tissues including the placenta [ 82 ]. CD147 is required for normal implantation by mediating gene expression in mouse uterine stromal cells during pregnancy [ 83 ].…”
Section: Sars-cov-2 and Pregnancymentioning
confidence: 99%
“… 4 CD147 is a potent inducer of angiogenic factors such as VEGF. 5 It induced the up-regulation of VEGF-derived foam cells, which may further promote intraplaque angiogenesis through the PI3K/AKT pathway. 6 A study indicated elevated CD147 in pressure-overloaded exacerbated RV dysfunction while suppressing CD147, and its ligand Cyclophilin A(CyPA) can meliorate RV dysfunction in PH model animals.…”
Section: Introductionmentioning
confidence: 99%